Siglec‐15 Regulates Osteoclast Differentiation by Modulating RANKL‐Induced Phosphatidylinositol 3‐Kinase/Akt and Erk Pathways in Association With Signaling Adaptor DAP12. (December 2013) - Kameda, Yusuke; Takahata, Masahiko; Komatsu, Miki; Mikuni, Shintaro; Hatakeyama, Shigetsugu; Shimizu, Tomohiro; Angata, Takashi; Kinjo, Masataka; Minami, Akio; Iwasaki, Norimasa
Abstract Siglecs are a family of sialic acid–binding immunoglobulin‐like lectins that regulate the functions of cells in the innate and adaptive immune systems through glycan recognition. Here we show that Siglec‐15 regulates osteoclast development and bone resorption by modulating receptor activator of nuclear factor κB ligand (RANKL) signaling in association with DNAX‐activating protein 12 kDa (DAP12), an adaptor protein bearing an immunoreceptor tyrosine‐based activation motif (ITAM). Among the known Siglecs expressed in myeloid lineage cells, only Siglec‐15 was upregulated by RANKL in mouse primary bone marrow macrophages. Siglec‐15–deficient mice exhibit mild osteopetrosis resulting from impaired osteoclast development. Consistently, cells lacking Siglec‐15 exhibit defective osteoclast development and resorptive activity in vitro. RANKL‐induced activation of phosphatidylinositol 3‐kinase (PI3K)/Akt and Erk pathways were impaired in Siglec‐15–deficient cells. Retroviral transduction of Siglec‐15–null osteoclast precursors with wild‐type Siglec‐15 or mutant Siglec‐15 revealed that the association of Siglec‐15 with DAP12 is involved in the downstream signal transduction of RANK. Furthermore, we found that the ability of osteoclast formation is preserved in the region adjacent to the growth plate in Siglec‐15–deficient mice, indicating that there is a compensatory mechanism for Siglec‐15–mediated osteoclastogenesis in the primary spongiosa. To clarify the mechanism of this compensation, we examined whether osteoclast‐associated receptor (OSCAR)/Fc receptor common γ (FcRγ) signaling, an alternative ITAM‐mediated signaling pathway to DAP12, rescues impaired osteoclastogenesis in Siglec‐15–deficient cells. The ligands in type II collagen activate OSCAR and rescue impaired osteoclastogenesis in Siglec‐15–deficient cells when cultured on bone slices, indicating that Siglec‐15–mediated signaling can be compensated for by signaling activated by type II collagen and other bone matrix components in the primary spongiosa. Our findings indicate that Siglec‐15 plays an important role in physiologic bone remodeling by modulating RANKL signaling, especially in the secondary spongiosa. © 2013 American Society for Bone and Mineral Research.